THE ROLE OF THE OUTSIDER IN CONTEMPORARY QUR’ANIC INTERPRETATION AND ITS INFLUENCE ON SHARI’A RULINGS - Azeez, Olalekan Rasheed; Olanrewaju, Yusuf Adam (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
Islam has been plagued by enemies who lie in wait, sparing no effort or expense to cast doubt upon it using various methods and techniques. The Islamic nation has faced significant threats from enemies since the Prophet's mission, including invasion of its thought, creed, heritage and history. Alienation in Exegesis (Tafsir) has caused confusion among Muslims, particularly in light of scientific discoveries, impacting rulings and the Qur'an's miraculous nature. This research examines the concept of infiltration and its effect on Islamic rulings. It explores the linguistic and terminological meaning of the word "Tafsir," the concept of "infiltration" linguistically and terminologically, its two types, and presents some examples of infiltration in Tafsir. The researcher discusses the potential impact of infiltration on Islamic rulings, suggesting methods to purify Tafsir and prevent misunderstandings of Islamic principles. The researcher used a presentation and deductive method to analyze Tafsir's works deemed infiltrated due to deviation from original principles, explaining their classification and correct interpretations. The researcher also deduced some effects that infiltration may have on Islamic rulings. In conclusion, the researcher reached several findings and recommendations, including the need to raise awareness of the dangers of infiltration and its destructive impact on the Book of Allah and its interpretation, the importance of strengthening religious education that focuses on proper methodology in Tafsir to prevent the infiltration of errors, and the necessity for scholars to review and scrutinize Tafsir works to ensure they are free of errors and infiltration.